Linking leader's emotional labour strategies with leader's attitude: an effective approach towards leadership. (2019) - Ahmad, Sajjad; Nisar, Qasim Ali; Imran, Asma; Waqas, Muhammad; Malik, Summaira
Emotions are important part of one's life and job. Emotions are always ready for feisty attack on individuals' attitudes at workplace. The present study aimed to investigate the impact of leader's emotional labour strategies on leader's attitudes by considering the mediating role of leader's job satisfaction. The data were collected by teachers of universities in Pakistan by using simple random sampling. Confirmatory factor analysis and structure equation modelling techniques had been used to evaluate the appropriate results. Results divulged that emotional labour strategies significantly influence the leader's attitudes. Moreover, surface acting is significantly and negatively associated with leader's organisational commitment and leader's loyalty. Similarly, deep acting and display of genuine emotions significantly and positively related to leader's organisational commitment and leader's loyalty. Path analysis results indicated that leader's job satisfaction partially mediate the relationship between emotional labour strategies and leader's attitudes.